Environmental Isolation of Sporothrix brasiliensis in an Area With Recurrent Feline Sporotrichosis Cases - Rabello, Vanessa Brito Souza; Almeida-Silva, Fernando; Scramignon-Costa, Bruno de Souza; Motta, Beatriz da Silva; de Macedo, Priscila Marques; Teixeira, Marcus de Melo; Almeida-Paes, Rodrigo; Irinyi, Laszlo; Meyer, Wieland; Zancopé-Oliveira, Rosely Maria (Frontiers in Cellular and Infection Microbiology, 2022)
Sporotrichosis has been expanding throughout the Brazilian territory in recent years. New outbreaks have emerged, and consequently, the sporotrichosis agents, mainly Sporothrix brasiliensis, should remain in the environment somehow. Therefore, the aim of this study was to investigate the presence of Sporothrix spp. in the environment from an area of ​​the Rio de Janeiro state, Brazil, with recurrent cases of human and animal sporotrichosis. Abandoned demolition timber wood samples were collected in the garden of a house where the cases of human and feline sporotrichosis have occurred in the last 10 years. The environmental survey revealed a Sporothrix spp. colony from the serial dilution cultures of one abandoned demolition wood sample. In addition, a fungal strain isolated from a cat with skin lesions that lived in the house was also included in the study. The species-specific PCR, and calmodulin partial sequencing identified the environmental and cat isolates as S. brasiliensis. Furthermore, the phylogenetic analysis performed with the partial sequences of internal transcribed spacer region and constitutive genes (calmodulin, β-tubulin, and chitin synthase) showed high similarity between environmental and cat isolates from the same geographic region. Moreover, the antifungal susceptibility test revealed that the minimal inhibitory concentration of itraconazole from the environment isolate was lower than the cat isolate, while amphotericin B and terbinafine were similar. Our results show that S. brasiliensis is able to maintain itself in the environmental material for years. With this, we corroborate that the eco-epidemiology of sporotrichosis is not well understood, and despite the major occurrence of S. brasiliensis in Brazil, it is rarely isolated from the environment.